If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2f + -6 = -5f + -3 Reorder the terms: -6 + -2f = -5f + -3 Reorder the terms: -6 + -2f = -3 + -5f Solving -6 + -2f = -3 + -5f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '5f' to each side of the equation. -6 + -2f + 5f = -3 + -5f + 5f Combine like terms: -2f + 5f = 3f -6 + 3f = -3 + -5f + 5f Combine like terms: -5f + 5f = 0 -6 + 3f = -3 + 0 -6 + 3f = -3 Add '6' to each side of the equation. -6 + 6 + 3f = -3 + 6 Combine like terms: -6 + 6 = 0 0 + 3f = -3 + 6 3f = -3 + 6 Combine like terms: -3 + 6 = 3 3f = 3 Divide each side by '3'. f = 1 Simplifying f = 1
| 11d+5=3d-3 | | 7z-6=3z+4 | | -8k+4=-6k+20 | | 9j-4=5j+28 | | -6u+7=u+70 | | y/5=-20 | | 11u+1=6u-29 | | -x-4=-4x+2 | | -8g+7=-g+63 | | 70=6x-14 | | 7j-4=3j-28 | | 10e-4=4e-10 | | 2a+4=-3a-36 | | -2q+6=3q-24 | | 2x-1=-x-28 | | 6h-4=h-9 | | 9y-1=5y+15 | | 12+8=5d+57 | | 7(3g+8)/4=35 | | 8-32x+27x-3=0 | | 4(x-5)=-1.6 | | 12d+8=8d+16 | | 13=5c-9 | | 9e-7=28.1 | | 8(x-2)=26.4 | | 2(3y-6)=-18 | | 2(7v-4)=-22 | | 3(4k-4)=60 | | 4(6u-4)=152 | | 3(5t+2)=-84 | | 5(4q+3)=-145 | | 8e-7=17 |